Assessment of Health-Related Quality of Life and Muscular Strength in Children with Beta Thalassemia - Eman Abdul hamzakhadier (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background:Thalassemia is an inherited blood disorder that requires regular blood transfusions and chelation therapy. These treatments can lead to restrictions in physical activities, social participation, and muscle strength. Quality of life, as measured by individuals’ own perceptions of their well-being and other aspects of life, can be significantly affected by thalassemia. Objective: To assess quality of life related to health, muscular strength and pain in children with beta thalassemia. Methods: We studied 60 children with beta thalassemia, aged 1 to 15 years. The quality of health-related life, including physical, emotional, and social performance, was assessed. Muscle strength was evaluated for all children using a standardized questionnaire. Both patients and their parents completed the questionnaire at baseline. Results:The study results showed that a significant number of participants (86.6%) had a family history of thalassemia. The majority (76.6%) had hemoglobin levels above 65%, and 88.3% required splenectomy. Most participants (83.3%) received chelation therapy, and 81.6% underwent monthly blood transfusions. Regarding psychological effects, 61.6% were affected, with 63.3% experiencing difficulty breathing and pallor. In terms of quality of life, 98.3% suffered from physical functioning issues, 78.3% from emotional problems, 73% from social difficulties, and 70% from pain and muscle weakness. Conclusion:The study concluded that thalassemia, a chronic disease, has a negative impact on the health-related quality of life (HRQoL) and muscle strength of children in different age groups.